Energy Processes, Systems and Equipment - Pietrowicz, Sławomir; Sówka, Izabela; Kolasiński, Piotr (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book focuses on the progress in modern energy processes, systems and equipment. Since the beginning of humankind, energy has been the most important need for each human and living being. Thus, the development of different ways of energy conversion that can be applied to cover growing energy needs has become a crucial challenge for scientists and engineers around the world, making the power industry, in which operation is based on subsequent energy conversion processes, one of the most important fields of the local, national, and global economy today. Progress in precise description, modeling, and optimization of physical phenomena related to the energy conversion processes bounded to large and dispersed power systems is a key research and development field of the economy.